PENINGKATAN EFISIENSI PELAYANAN PUBLIK DI DAERAH: PRIVATISASI ATAU OPTIMALISASI BUMD ? Belajar dari Kasus Perusahaan Daerah Air Minum - -, Nindyantoro - (Jurnal Manajemen Pembangunan Daerah, 2009)
Efficient public service can be achieved by private or state company, depend on the competency of the service. There are some theories explain the public service efficiency; the ownership theory, public choice theory and organization theory. In the case of PDAM (Perusahaan Daerah Air Minum - Municipal Waterworks), external and internal factors are the source of a non optimal service. External factors are: local government multi role (as operator and regulator), the double role as a company and official agency, monopolistic market, single shareholder, political driven tariff, and ineffective community control. Those external factors affect the internal PDAM such as work motivation based on sense of belonging and incentive structure, spirit of innovation, and service and customer orientation service. Therefore a clean water service regulation is required in order to get dynamic competition, tariff which support company financial condition and high efficiency followed by fair and broad scope of service. Keyword: privatization, efficiency, organization.